A Rare Clinical Entity of Krukenberg Tumor: A Case Report in Margono Soekarjo Hospital of Purwokerto - Aditya Eka Octavian; M Yamsun; Gita Nawangtantrini (Indonesian Journal of Cancer, 2023)
Introduction: Krukenberg Tumor is an ovarian tumor that originated from other organ metastases such as gastric, colorectal, pylorus, appendix, colorectal, or breasts. This study aims to report an incidence of a Krukenberg tumor found in a-36year- old woman who has finished her therapy at Margono Soekarjo Hospital.Case Presentation: This case reports the incidence of a Krukenberg tumor found in a-36-year old woman with the main complaint of a burning sensation in her stomach and the existence of a mass in the right and under the Arcus Costae. The patient underwent metastasectomy and biopsy. Histopathological examinations show that the features of Krukenberg tumor originated from a gaster. The patient then underwent chemotherapy for 6 cycles, radiotherapy 20 times, and some evaluation. This case had been observed for 12 months since the first time the patient came to the hospital.Conclusions: Krukenberg tumor is a rare tumor of the ovary which is characterized by poor prognosis. This case depicts the finding of Krukenberg tumor with gastric clinical features. The combination of metastasectomy and chemotherapy can be done in such a case to improve patient survival rates.